Self Assessment System : Upaya Edukatif Badan Pengelola Keuangan dalam Meningkatkan Penerimaan Pajak Perhotelan di Aceh Tengah - Noviardi, Ikhwan; Jannati, Sri (MASALIQ, 2021)
Hotel tax is a promising source of Regional Original Revenue (PAD) for Central Aceh district. Central Aceh as a tourist destination area that is always crowded with tourists makes hotels always full, especially during the holiday season. Until now, the hotel and lodging business in Central Aceh is growing and continuing to grow. If managed properly, this opportunity can certainly be utilized by the Central Aceh district government in increasing hotel tax revenue. However, based on the initial data collected, there are obstacles in hotel tax collection and there are significant fluctuations in hotel tax revenue. The purpose of this study was to find out how the efforts of the Central Aceh District Financial Management Agency increased hotel tax revenue and how hotel taxes contributed to Central Aceh District PAD. This research is a qualitative research with descriptive method. Source of data in this research is primary and secondary data. This research was conducted at the Central Aceh Regency Financial Management Board, Bunda hotel and Jeddah hotel. The results of this study indicate that the "self assessment system" tax collection system implemented by the Central Aceh District Financial Management Agency is not optimal in increasing hotel tax revenues. The facts found actually hotel tax revenue fluctuated and did not reach the target. The amount of tax deposited by the taxpayer is not in accordance with what it should be. This has an impact on the contribution of hotel taxes to Central Aceh district PAD for the past five years, which is included in the very low criteria. For this reason, the Central Aceh District Financial Management Agency continues to educate taxpayers by building awareness of paying taxes according to actual conditions. In addition, the financial management agency also made improvements to the hotel tax revenue management system, improved monitoring systems and improved law enforcement for non-compliant taxpayers.